2020
DOI: 10.5812/msnj.100567
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spiritual Care on the Spiritual Health of Adolescents with Cancer: A Pre-Experimental Study

Abstract: Background: Spiritual health is considered one of the most important components of health and palliative care that facilitates harmonious and integrated communication among one's inner forces. One of the basic principles of holistic nursing care is to pay attention to the spirituality and spiritual care of patients. Spiritual care is an important source of adaptation in refractory and chronic patients such as cancer. Objectives: The aim of this study was to determine the effect of spiritual care on the spiritu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…(26) Another correlational study has showed that cancer patients undergoing chemotherapy who had a high religious/spiritual coping score were found to have a higher level of hope. (27) The results of a study by Mansurifard and colleagues indicated spiritual health of adolescents with cancer was promoted following spiritual cares, (28) which is in line with our study. However, the findings of our study is not similar to a study by Kang and colleagues, in which meaning of life of adolescents with advanced cancer had been improved following logo therapy, however, no significant changes were observed for spiritual well-being in both the intervention and control groups.…”
Section: Discussionsupporting
confidence: 90%
“…(26) Another correlational study has showed that cancer patients undergoing chemotherapy who had a high religious/spiritual coping score were found to have a higher level of hope. (27) The results of a study by Mansurifard and colleagues indicated spiritual health of adolescents with cancer was promoted following spiritual cares, (28) which is in line with our study. However, the findings of our study is not similar to a study by Kang and colleagues, in which meaning of life of adolescents with advanced cancer had been improved following logo therapy, however, no significant changes were observed for spiritual well-being in both the intervention and control groups.…”
Section: Discussionsupporting
confidence: 90%
“…Spiritual care is one of the most important aspects for health, the spiritual aspect has a harmonious relationship and is interconnected with life stability and inner strength, provides peace, strengthens relationships with oneself, community gods, and the environment. Spiritual care is the only force in coordinating the physical, psychological and social dimensions [25], [46].…”
Section: Discussionmentioning
confidence: 99%
“…The validity test gets the Cronbach's alpha value is 0.85 [38]. The DASS 42 questionnaire taken number (2,4,7,9,15,19,20,23,25,28,30,36,40,41) with normal anxiety assessment indicators with a value range of 0-7, mild anxiety 8-9, moderate anxiety 10-14, severe anxiety 15-19, and very severe anxiety >20 [39]. A description of the DASS assessment of one's perceived results starting with the number 0: Absent or never, 1: According to what is experienced to a certain degree, or sometimes, 2: Often, and 3: Very much according to what is experienced or almost every time it is experienced.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations